PENGARUH PEMBERIAN PUPUK ORGANIK CAIR BONGGOL PISANG TERHADAP PERTUMBUHAN TANAMAN KANGKUNG DARAT (Ipomoea reptans Poir) - Ariandani, Nunung; Fajri, Nurul (Cocos Bio, 2021)
Based on the purpose of this study, namely to determine “The Effect Of Liquid Organic Fertilizer On The Growth Of Land Kale Plant (Ipomoea reptas Poir)”. This study used a completely randomized design (CRD) with 10 replications. In the control media treatment without using liquid organic fertilizer while in the experimental media using liquid organic fertilizer with each different concentration .data analysis used the T test at a significan level of 5%. The results of this study showed that the growth on syem height of land kale plants averaged 4 days in control A, while in experimental B the concentration of 20 ml averaged 5,1 days, and experimental C concentration of 25 ml averaged 5,4 days and experimental D concentration of 30 ml an averaged of 6,8 days. While the results of the study on the number of leaves with control A average of 3,2 days, while in experimental B the conzentration of 20 ml averaged 3,6 days, and axperimental C the concentration of 25 ml averaged 3,8 days, and experimental D the concentration 30 ml an average of 4,4 days. This shows that the content of liquid organic fertilizer from banana weevil waste has no effect on the growth of land kale plants. Keywords: POC, Banana Weevil, Growth Of Land Kale